Walter Benjamin e a questão da alteridade : rastro, história e memória - Bortolini, Bruna de Oliveira (2020)
This doctoral thesis deals with aspects relevant to the development of research around the notion of Alterity in Walter Benjamin. Therefore, part of the survey and analysis of such aspects by means of the author's essay Theses on the Philosophy of History (Über den Begriff der Geschichte, 1942), even though they are not limited to this work and can also be found in his other writings. Among the analyzed aspects stand out focusing on the so-called "traces" or "ruins" of History, elements that constitute both as historical facts, as by natural material objects, resistant to classification and universalization processes. For that reason they can only be found outside conventional historiography. The research also highlights the constelational method, the sense of origin (Ursprung), temporality, memory or remembrance (Erinnerung), narrative and citability, a constellation of elements inseparable from each other, of great importance to research of the proposed theme. It also briefly exposes the concept of Alterity to be worked on, represented largely by the philosophy of Emmanuel Levinas. The study, by promoting a dialogue between these authors around the notion of Alterity, reveals a very peculiar way or structure of understanding reality. This is a way of understanding that has as starting point the real itself in its concreteness and temporality, in addition to the concern with minorities and those elements considered less relevant to the study of History and the development of human relations.